STRATEGI TESLA MENGHADAPI DAMPAK POLITIK ELON MUSK - Sarjono, Haryadi; Setiawan Soeratin, Boyke; Amandio, Daniel; Kennedy Lim, Dicky; Gouw, Samuel (Jurnal Bisnis Darmajaya, 2025)
This study analyzes the impact of Elon Musk’s political involvement on Tesla Inc.’s financial stability and investor sentiment. Using a descriptive qualitative approach through document analysis, the research employs secondary data from financial reports, NASDAQ stock movements, and reputable media sources. Findings show that Musk’s political activity heightened stock volatility, contributed to a 9% revenue decline, and led to a 71% drop in net income in Q1 2025. Tesla’s strong association with Musk intensified market sensitivity, triggering retail panic selling and portfolio adjustments by institutional investors. Political uncertainties also weakened automotive margins and increased R&D pressures. The study recommends stronger corporate governance, greater transparency, CEO succession planning, and strategic diversification to mitigate risk. Overall, the results highlight the importance of leadership-crisis management and proactive communication in maintaining investor confidence.